PENGARUH PRODUCT REVIEW DAN VIRAL MARKETING TERHADAP PURCHASE INTENTION PRODUK SKINCARE MEREK LOKAL INDONESIA (Studi Kasus Pada Pengguna Aplikasi Media Sosial TikTok) - Riska Dinda Anissa; Rudy P. Tobing (Bajang Institute, 2022)
The phenomenon of technological development that occurs has an impact on changes in consumer behavior in carrying out purchase activities. This study aims to determine the influence of product reviews and viral marketing on the purchase intention of skincare products of local Indonesian brands. Design / methodology / approach: This study used a causal associative quantitative approach with a total sample of 100 respondents. The instrument used was a questionnaire containing 28 statements. Instrument testing uses validity tests and reliability tests. Data analysis uses descriptive and correlation analysis, while hypothesis testing uses multiple linear regression analysis. Results: The results showed that: 1. product reviews did not have a positive and insignificant effect on the purchase intention of local Indonesian brand skincare products. 2. Viral marketing has a positive and significant effect on the purchase intention of skincare products of local Indonesian brands. 3. Product reviews and viral marketing simultaneously have a positive and significant effect on the purchase intention of local Indonesian brand skincare products. Limitations of research / implications: The limitations in sampling this study are only in respondents who are users / have used / are interested in using 5 local Indonesian brand skincare products only, namely; Avoskin, Lacoco, Wardah, Somethinc, and Sensatia Botaicals. As well as only within the scope of TikTok social media users. Since this research was carried out in a business field with the field of marketing management, it can be concluded that the results of this study certainly have implications in business and for subsequent research.